Difference of hydrodynamic force on foot between front crawl six-beat and flutter kicking - Ichikawa, H.; Kuriki, A.; Taba, S.; Taguchi, M. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The purpose of this study was to investigate the hydrodynamic difference between six-beat kick in front crawl swimming and flutter kick without rolling of the whole body. The subject was a male college swimmer. Two pairs of small pressure sensors were attached on the dorsal and plantar sides of both of the swimmer's feet during trials, which involved flutter kick while holding a kickboard and six-beat crawl swimming. The motion of the swimmer's right leg and arm was recorded using an underwater video camera during the trials. In the six-beat trials, the positive and negative peak values of the difference of pressure between dorsal and plantar sides were not similar in the three downbeats and upbeats during one stroke cycle. lt was suggested that there were hydrodynamic differences between flutter kick and six-beat kick in front crawl swimming.